Persepsi Mahasiswa Terhadap Praktik Pengungkapan Sukarela dengan Non Profit Organizations Reporting Index di Universitas Bangka Belitung - Wenni Anggita; Anggraeni Yunita; Erita Rosalina; Izma Fahria (UNSIKA (Universitas Singaperbangsa Karawang), 2018)
The services provided by nonprofit organizations and their ability to continue providing such services, how managers carry out their responsibilities for the performance of nonprofit organizations. This research aims to analyze the perception of Bangka Belitung University students about the voluntary disclosure practices at Bangka Belitung University by Non Profit Organizations Reporting Index. As one of the Non Profit Organizations, the collage became one of the entities of interest to be discussed. The research using qualitative approach by distributing quetionnaires. The sample used is 978 faculty of economics students who are familiar with voluntary disclosure. The result showed that Bangka Belitung University doesn’t use Non Profit Organizations Reporting Index in the report. Students agreed that a non profit organization, the university should be know the informations needed by stakeholders. Of the five indicators mentioned in Non Profit Organizations Reporting Index used in this study, tey agree that financial and non financia information is important to be informed openly.